The Life Cycles of Mayflies of the Eastern Ukraine. Subfamily Baetinae (Ephemeroptera, Baetidae) - Martynov, A.V. (Вестник зоологии, 2013)
The life cycle types of mayflies of the subfamily Baetinae in Eastern Ukraine are determined. The scheme for identification of larval age structure is given. The age structure changes of Baetis braaschi, B. nexus and Alainites muticus larvae during the year are described in detail. The flight periods of imagoes throughout the studied region are delimited for almost all species of the subfamily. B. braaschi is shown to have the bivoltine life cycle, with its populations overwintering as the larval stage (MBws) independently on temperature conditions in the water body. The peculiarities of oviposition are described for this species. The following aspects of life cycles were revealed: nymphs, subimagoes and imagoes of different generations of B. braaschi differ considerably in size; the voltinity of B. vernus in the region can vary (Us and/or MBss), mainly due to temperature conditions of the water bodies, where its development takes place; geographically isolated populations of A. muticus in the Eastern Ukraine reproduce only by thelytoky.